Ecological security assessment of Qinzhou coastal zone based on Driving forces-Pressure-State-Impact-Response (DPSIR) model - Zhou, Jiaodi; Wang, Xilong; Lu, Dongliang; Dan, Solomon Felix; Kang, Zhenjun; Xu, Yuping; Weng, Peiyao; Wei, Zhaofu (Frontiers in Marine Science, 2022)
A coastal zone represents the intersection of ocean and land, and is characterized by high primary productivity, biodiversity, and rich resources but with strong sensitivity and vulnerability of the natural environment. In this study, 29 indicators reflecting the status of ecological security were selected to construct an ecological security evaluation index system using the Driving force Pressure State Impact Response (DPSIR) model. The comprehensive index method was used to evaluate the ecological security of Qinzhou coastal zone from 2011 to 2020 and to explore the driving factors of its evolution. The results showed that (1) In the past 10 years, the ecological security of Qinzhou coastal zone fluctuated and developed, and the security level changed from early warning – safer – more dangerous – early warning to safer; and the security level was the lowest (0.361) in 2014. The main reason was the impact of ecological marine disasters, such as three red tides with the eutrophication index of seawater as high as 4.170. (2) Since 2015, the ecological security of the coastal zone has shown an upward trend, which was mainly due to the implementation of the newly revised environmental protection law in the same year, the comprehensive promotion of “The 13th Five-Year Plan for environmental protection”, and a series of measures related to the construction of ecological civilization and environmental protection, which provided a strong guarantee for the ecological security of the coastal zone. This study proposes measures to promote the better development of the ecological environment of Qinzhou coastal zone.